'Lower types of cranks, crooks and racial bigots'? The Universal Negro Improvement Association and black political violence in the United States, 1918–1930. (10th February 2020) - Lennon, Thomas P.
Abstract : This article examines the involvement of the black nationalist Universal Negro Improvement Association (UNIA) in black political violence in the early-interwar period in the United States. Evidence suggests that the UNIA was the organisation most often involved in black political confrontations, and the article discusses how the state, the black and white press and other black activist organisations may have both benefitted from and perpetuated the UNIA's reputation for political violence. The essay argues that the UNIA's involvement in violence against other black organisations and groups can be explained partly by the intensity of the 'war of words' among prominent black leaders in the United States, such as W.E.B. Du Bois and Marcus Garvey. Furthermore, the article suggests that ethnic and gender differences within the American UNIA itself could exacerbate pre-existing tensions between different groups of Garveyites. Contextualising black political violence in these ways allows us to move beyond a reductionist view of grassroots Garveyites as prone to violence. Instead, this approach allows us to better understand the relationship between the famous 'war of words' and the kinds of tensions, confrontations and violence that sometimes occurred at grassroots level between supporters of different black organisations and groups. The article contributes not only to the growing historiography about the UNIA at grassroots level, but also to discussions about the militarisation of black protest during World War I and in the 1920s, including the use of self-defence and paramilitary-style tactics by people of African descent in the United States.